FOSTERING THE LISTENING SKILL OF INDONESIAN NINTH GRADERS OF JUNIOR HIGH SCHOOL THROUGH DICTOGLOS - Leniadi, Ni Made (Yavana Bhasha : Journal of English Language Education, 2019)
This study aimed at improving the students’ listening skill through Dictoglos. The design of the study was a classroom based action research which was carried out in two cycles, each comprising two teaching learning sessions and one post-test. The subjects were the ninth year students of SMP Negeri 1 Rendang at class IX D. The data were collected through listening test and  analyzed descriptively. The results revealed that the students’ listening skill could be improved through the use of  Dictoglos as proven by attainment of  the class success indicator(class learning mastery level) 90% by the end of cycle 2, which was improving from  67% in cycle 1 and 47% in the pretest.